Uniform Workload Distribution Problems - Czimmermann, Peter; Pesko, Stefan; Cerny, Jan (Communications - Scientific letters of the University of Zilina, 2016)
In this paper we review common studies from the years 1984-2015 of problems occurring in uniform scheduling of workload distributions. These problems were formulated first by Pesko in dealing with the practical problem of regular scheduling of service vehicles. Given the nonnegative, real matrix with daily records of vehicles as columns, we need to minimize some irregularity measure of row sums (workloads) by permuting matrix columns. The problem has various practical modifications, such as the weighted rows of matrix, workload uncertainty variance, graph approach of exchange of elements and generalized inverse formulations. Some of them are presented in the paper.